Temperature-Dependent Development And Freezing Survival Of Protostrongylid Nematodes Of Arctic Ungulates: Implications For Transmission - Kafle, Pratap; Orsel, Karin; Peacock, Stephanie J.; Grond, Sarah; Kutz, Susan (Zenodo, 2018)
Data used to derive the conclusion of the work. Spreadsheets contain raw data.